The Next Level of Purchase Intention - Elfindah Princes , Adler Haymans Manurung , Idris Gautama So , Sri Bramantoro Abdinagoro (International Journal of Advanced Science and Technology, 2020)
Purchase Intention is always associated with the capabilities of the firms to approach thecustomers through brand image, commercial activities and how firms provide excellent serviceto increase customer satisfaction and increase the purchase intention probability for the nextproduct release. Customers are viewed as the object of firms' organizational activities to providebenefits for the company. The researcher broadens this view into a bigger perspective, where thecustomers are now not only becoming the objects, but also the subjects of the organizationalactivities. The purchase intention must move on to the next level where all actors inorganizational activities are taking charge in delivering purchase intention. Human - to - humaninteraction has become so important in organizational activities that firms must articulate onthese factors to complement the existing factors, especially during the Industry 4.0. This researchuses a quantitative analysis with 91 respondents aged between 18 to 55 years old with income.The data analysis uses SPSS AMOS. The findings correlate with the newest Consumer TrendReport for 2020 and more that in the future, social interaction between humans takes a greatdeal in making purchase decisions, known as consumer conformity. Innovations must be done bygaining consumer insights and increasing social roles to the advantages of the firms throughsocial comparison, image related concerns and strategic complements. This research has severallimitations. First, data collection was based on convenience sampling and the second, the idealnumber of respondents should be 385 based on Cochran's sampling method calculation. Futureresearch should address these two issues.